FECUNDITY FLUCTUATIONS IN THE OIL-SARDINE, SARDINELIA LONGICEPS VAL. - Raja, B T Antony (Indian Journal of Fisheries, 2011)
The functional relationship between fecundity and length in the oil-sardine iscurvilinear and that between fecundity and weight is rectilinear. Comparing the relativemerits of the two relationships, the study has revealed that it cannot be held thatthe fecundity,-weight relationship is better as a rule. On the other hand, a comparisonmade of expected fecundity and weight ad'usted to a common length shows that, in general,the heavier fish of identical length are more fecund. For a given length or weight thefecundity variations are considerable.